2006
DOI: 10.1007/s11664-006-0152-7
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic growth kinetics for Sn-Ag, Sn-Cu, and Sn-Ag-Cu lead-free solders on Cu, Ni, and Fe-42Ni substrates

Abstract: Soldering with the lead-free tin-base alloys requires substantially higher temperatures (;235-250°C) than those (213-223°C) required for the current tin-lead solders, and the rates for intermetallic compound (IMC) growth and substrate dissolution are known to be significantly greater for these alloys. In this study, the IMC growth kinetics for Sn-3.7Ag, Sn-0.7Cu, and Sn-3.8Ag-0.7Cu solders on Cu substrates and for Sn-3.8Ag-0.7Cu solder with three different substrates (Cu, Ni, and Fe-42Ni) are investigated. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 23 publications
1
22
1
Order By: Relevance
“…Since 84-3-3-10 solder alloys contained more In than 89-3-3-5, the higher In content can be reasonably assumed to inhibit the dissolution of Cu. The apparent activation energies in this study were of the same order of magnitude as the apparent activation ener- gies, 28.9 kJ/mol, in In49Sn/Cu [15], 22.2 kJ/mol in SnCu/Cu and 38.1 kJ/mol in SnAgCu/Cu [27]. The apparent activation energy obtained from the aforementioned data on Pb-free solders still differed from our results by a factor of two.…”
Section: Resultscontrasting
confidence: 66%
“…Since 84-3-3-10 solder alloys contained more In than 89-3-3-5, the higher In content can be reasonably assumed to inhibit the dissolution of Cu. The apparent activation energies in this study were of the same order of magnitude as the apparent activation ener- gies, 28.9 kJ/mol, in In49Sn/Cu [15], 22.2 kJ/mol in SnCu/Cu and 38.1 kJ/mol in SnAgCu/Cu [27]. The apparent activation energy obtained from the aforementioned data on Pb-free solders still differed from our results by a factor of two.…”
Section: Resultscontrasting
confidence: 66%
“…Consequently, IMC phases start to nucleate and grow at the interface. 20 The chemical composition of the IMCs revealed that they were composed of Cu and Sn atoms. EDS analysis was carried out to identify the IMCs at the interface.…”
Section: Resultsmentioning
confidence: 99%
“…Since Sn-rich solders have excellent solderability on Cu, Cu substrate has been widely used in electronic assembly. Typically, during the soldering of Sn-Cu solder systems on Cu substrate, ƞ-Cu6Sn5 and ɛ-Cu3Sn phases are common interfacial layers that form between the solder/Cu substrate [5,59,88,89]. During the liquidsolid interaction of molten solder and Cu substrate, it is believed that a rapid dissolution of Cu into molten solder with a lower Cu concentration occurs immediately after the Cu oxide film has been removed by the actions of the flux.…”
Section: Interfacial Intermetallic Compound (Imc) Layer Of Reinforcedmentioning
confidence: 99%